1988
DOI: 10.1177/026624268800600304
|View full text |Cite
|
Sign up to set email alerts
|

Black Business in South Africa: A Challenge to Enterprise

Abstract: Bruce Philips is a lecture in business policy and helene brice is a senior lecture in marketing in the department of Business Science at the University of Cape Town South africa. Black business in south afrrica represetns a paradox-it forms a small minority group in the overall business structure of South African society yet it is required to serve the interest of the majority of the peple of that society. The authors have drawn on the experiences of black business ment in one of the major metropolitian centre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…This aspect of culture, which represents the norms, values and beliefs of the largest segment of the South African population -Black Africans, contradicts Hofstede's dimensions related to masculinity and individualism. Phillips and Brice (1988) further corroborate these contrasting views between Whites and the Black community. However, as Swartz and Davies (1997) argue, we should not see Ubuntu as a panacea, nor assume that it resonates with all South Africans.…”
Section: The Social Dimensionsupporting
confidence: 66%
See 1 more Smart Citation
“…This aspect of culture, which represents the norms, values and beliefs of the largest segment of the South African population -Black Africans, contradicts Hofstede's dimensions related to masculinity and individualism. Phillips and Brice (1988) further corroborate these contrasting views between Whites and the Black community. However, as Swartz and Davies (1997) argue, we should not see Ubuntu as a panacea, nor assume that it resonates with all South Africans.…”
Section: The Social Dimensionsupporting
confidence: 66%
“…was a sector vital for socializing and job creation. Phillips and Brice (1988) echo this view of discriminatory laws shaping Black business. Morris and Pitt (1995) suggest that the informal sector accounted for close to 4 million jobs in 1990, with 22 percent of the active black population engaged in informal sector activities.…”
Section: Resultsmentioning
confidence: 91%
“…School graduates tended to join the industrial and civil service sector, where there were fewer raids and intimidation by the police and few if any attacks by the radical youth for collaborating with the 'system'. This is supported by Phillips and Brice (1988) who found that a socialist orientation is the basis of the Black community and as a result they are likely to exhibit behavioural patterns that are essentially co/operative or group focused. This is quite unlike the individualistic competitive patterns of the White community, which appears to have been adopted from its Western heritage.…”
Section: Entrepreneurshipmentioning
confidence: 84%